Routine Bone Biopsy during Percutaneous Vertebroplasty or Kyphoplasty in the Treatment of Osteoporotic Vertebral Fractures. Does it Change the Management Plan? Do we Know the Costs?. Issue 1 (April 2016) - Shakokani, Majeed; Robinson, Tom; Cumming, David; Lovell, Robert; Bhagat, Shaishav; Powell, John; Kaleel, Saajid
Introduction: According to the WHO, osteoporosis causes more than 8.9 million fractures annually worldwide. The lifetime risk for a wrist, hip or vertebral compression fracture (VCF) has been estimated to be in the order of 30% to 40% in developed countries. It is estimated that up to 2 people per 100, 000 in England are currently treated with percutaneous vertebroplasty and percutaneous balloon kyphoplasty. There are other causes of vertebral compression fractures, and therefore a bone biopsy is recommended to rule out pathologies such as malignancy. There is debate about the necessity of routine biopsy and its cost- effectiveness. Material and Methods: We conducted a retrospective study on a cohort of consecutive patients undergoing vertibroplasty/kyphoplasty and bone biopsy over a 2 year period between 2013 and 2015 at The Ipswich Spinal Unit. Patient's demographics, indication for surgery, level of augmentation, histopathology results, complications and outcomes were extracted from electronic records. Patients were grouped in to 2 major groups; suspected malignancy and unsuspected malignancy group. Subgroups included non-biopsy group, and routine biopsy group. The non-biopsy group was followed up until last point of care. Cost of a routine biopsy was calculated based on theater, surgeon, consumables and histopathology costs. Results: 64 patients, Mean age of 64, 129 levels were augmented, length of stay of 3 days, follow up of 22 weeks, and mean last point of care was 60 weeks. All underwent imaging and were discussed in a multi-disciplinary meeting (MDT). Out of the 64 patients, 22 malignancy group, 18 patients underwent biopsy. Out of the 42 patients in whom malignancy was not suspected, routine biopsy was performed in 17 patients. No malignancies (0%)found in the unsuspected malignancy group vs 5 positive samples in the suspected group. Routine biopsy did not change the management plan. Average Total cost of a routine biopsy was between £210 and £310. Conclusion: Contrary to the previously published reports, our study shows that there is no specific role for routine biopsy during vertebroplasty procedure. This is a reflection of our MRI reporting and MDT approach. Therefore, we believe selective biopsy is more cost effective and value added approach in vertebral compression fractures.